Studi Prakiraan Beban Listrik Pada Wilayah PLN Kota Pekanbaru Dengan Metode Mikro Spasial - Ardiyansyah Ardiyansyah; Dian Yayan Sukma; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Network development especially the substation can not be separated from the problem of area availability and load which is served on those areas. The placement of the substation should be located close to load centers, so it have network with a wide local area service. To determine area's load center of the next few years can be used with forecast of the long-term electrical loads using micro-spatial method, this method divides the load area into a view grid according to reign administration is the sub-district. This method uses datas related to electricity, socioeconomic, and demographic. In determining the grid peak load (districts) is calculated based on four groups of loads (sectoral). these are the household sector, industrial, commercial, and social. The approach taken in the micro-spatial method uses multiple linear regression model. To follow the trend of land use, then use the dependent variable with peak load's density. Results of peak load density is associated with the land use every sector, for peak load on those area. peak load forecast results for the city of Pekanbaru from 2015 to 2024 indicates a growth rate that varies every area from 4.3% to 20.9%, and growth of peak load average based on sectoral, are household sector 9.22%, industry 13.28%, commercial 7.95%, and social 9.39%. While the peak load of Pekanbaru City increased from 320.6 MVA in 2015 into 717.5 MVA in 2024.Keywords: Electricity load forecast, Micro spatial, sectoral.